Isolation and characterization of a temperature-sensitive dnaK mutant of Escherichia coli B. - Itikawa, H (1979)
A temperature-sensitive dnaK mutant (strain MT112) was isolated from Escherichia coli B strain H/r30RT by thymineless death selection at 43 degrees C. By genetic mapping, the mutation [dnaK7(Ts)] was located near the thr gene (approximately 0.2 min on the may). E. coli K-12 transductants of the mutation to temperature sensitivity were assayed for their susceptibility to transducing phage lambda carrying the dnaK and/or the dnaJ gene. All of the transductants were able to propagate phage lambda carrying the dnaK gene. When macromolecular synthesis of the mutant was assayed at 43 degrees C, it was observed that both deoxyribonucleic acid and ribonucleic acid syntheses were severely inhibited. Thus, it was suggested that the conditionally defective dnaK mutation affects both cellular deoxyribonucleic acid and ribonucleic acid syntheses at the nonpermissive temperature in addition to inability to propagate phage lambda at permissive temperature.